Pendaftaran Tanah Atas Tanah Hak Milik sebagai Sarana Kepastian Hukum Menurut Undang-Undang Pokok Agraria - Nadya Uli Lumban Tobing; Besty Habeahan (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2026)
Land registration is a crucial mechanism in realizing legal certainty over land rights, particularly land with ownership status (hak milik). The Basic Agrarian Law (Undang-Undang Pokok Agraria/UUPA) Number 5 of 1960 explicitly regulates land registration as an effort to provide legal protection and certainty of rights for landowners. The purpose of this study is to understand the procedures of land registration for ownership rights to ensure legal certainty for landholders, as well as to identify the obstacles encountered in the registration process that hinder the achievement of such certainty. This study employs a normative legal research method by examining primary and secondary legal materials. The research focuses on analyzing regulations related to land registration to provide legal certainty, in accordance with the provisions of the Basic Agrarian Law (UUPA) No. 5 of 1960 and its implementing regulations, such as Government Regulation No. 24 of 1997 concerning Land Registration. The findings of this study indicate that the procedures for land registration both sporadic and systematic (through the Complete Systematic Land Registration Program or PTSL) function to ensure legal certainty and protect ownership rights. However, several challenges arise in its implementation, including low public awareness, land disputes or overlapping ownership claims, limited resources at land offices, and financial and time constraints. Therefore, to achieve the intended objectives, improvements in the administrative system of the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) are required, along with increased public awareness regarding the importance of land certification.